Evaluation of Erythrocytes, Platelets, and Serum Iron Profile in Dogs with Chronic Enteropathy. (13th July 2010) - Marchetti, Veronica; Lubas, George; Lombardo, Andrea; Corazza, Michele; Guidi, Grazia; Cardini, Giovanni
Abstract : The aim of this study is to evaluate iron status, erythrocyte, and platelet modifications in dogs with chronic enteropathy (CE). Dogs were grouped as food-responsive diarrhea (FRD, n = 11 ), antibiotic-responsive diarrhea (ARD, n = 5 ), and steroid-responsive diarrhea (SRD, n = 6 ) relating to therapeutic-response. Clinical and haematological findings, evidence of gastrointestinal blood loss, and iron metabolism were evaluated before and after treatment. A mild normocytic or microcytic anemia and thrombocytosis were identified, respectively in 18.0% and 31.8% of CE dogs. No significant differences between pre- and posttreatment of hematocrit, haemoglobin, and mean corpuscular volume, platelet count and mean platelet volume were found. Statistical analysis pointed out significant differences between pre- and posttreatment in serum iron (P < .03 ) and unsaturated iron binding capacity (UIBC) (P < .01 ). No significant correlations were found between these parameters and canine Inflammatory Bowel Disease activity index and pattern of CE as well.